Critical Limb Ischaemia Exacerbates Mitochondrial Dysfunction in ApoE–/– Mice Compared with ApoE+/+ Mice, but N-acetyl Cysteine still Confers Protection. (October 2019) - Lejay, Anne; Charles, Anne-Laure; Georg, Isabelle; Goupilleau, Fabienne; Delay, Charline; Talha, Samy; Thaveau, Fabien; Chakfé, Nabil; Geny, Bernard
Abstract : Objectives: The current study was performed in order to determine the influence of hypercholesterolaemia on critical limb ischaemia (CLI) and whether targeting oxidative stress by antioxidant therapies such as N-acetyl cysteine (NAC), considered to be a direct scavenger of reactive oxygen species, could confer muscle protection. Methods: Apolipoprotein E (ApoE)–/– mice ( n = 9, 29 weeks old) and their genetic controls ApoE+/+ mice ( n = 9, 29 weeks old) were submitted to sequential right femoral and iliac ligations; the left limb served as control. ApoE+/+ mice were divided into two groups: Group 1 ( n = 4) and Group 2 ( n = 5); as well as ApoE–/– mice: Group 3 ( n = 3), and Group 4 ( n = 6). NAC treatment was administered to Groups 2 and 4 in drinking water. Mice were sacrificed on Day 40 and gastrocnemius muscles were harvested to study mitochondrial respiration by oxygraphy, calcium retention capacity by spectrofluorometry, and production of reactive oxygen species by electron paramagnetic resonance. Results: CLI associated with ApoE deficiency resulted in more severe mitochondrial dysfunction: maximum oxidative capacity and calcium retention capacity were decreased (−42.9% vs. −25.1%, p = .010; and −73.1% vs. −40.3%, p = .003 respectively) and production of reactive oxygen species was enhanced (+63.6% vs. +41.4%, p = .03) in ApoE–/– mice compared with ApoE+/+ mice respectively. Antioxidant treatment restored oxidative capacity, calcium retention capacity and decreased production of reactive oxygen species in both mice strands. Conclusions: In this small murine study, hypercholesterolaemia exacerbated mitochondrial dysfunction, as clinically expected; but antioxidant therapy appeared protective, which is counter to clinical experience. Further work is clearly needed.